2009
DOI: 10.1161/strokeaha.108.539155
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Hyperacute Blood Pressure and Outcome After Ischemic Stroke

Abstract: Background and Purpose-High blood pressure (BP) is associated independently with poor outcome after acute ischemic stroke, although in most analyses "baseline" BP was measured 24 hours or more postictus, and not during the hyperacute period. Methods-Analyses included 1722 patients in hyperacute trials (recruitment Ͻ8 hours) from the Virtual Stroke International Stroke Trial Archive (VISTA) Collaboration. Data on BP at enrolment and after 1, 2, 16, 24, 48, and 72 hours, neurological impairment at 7 days (NIHSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
85
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 14 publications
13
85
5
Order By: Relevance
“…Large falls in blood pressure or increases in blood pressure were associated with a higher risk of poor outcomes. Similarly, the authors of the Virtual International Stroke Trial Archive collaboration 8 recently found that high systolic pressures, a small drop in systolic pressure, and large variability in systolic pressure were associated with poor outcomes.…”
mentioning
confidence: 91%
“…Large falls in blood pressure or increases in blood pressure were associated with a higher risk of poor outcomes. Similarly, the authors of the Virtual International Stroke Trial Archive collaboration 8 recently found that high systolic pressures, a small drop in systolic pressure, and large variability in systolic pressure were associated with poor outcomes.…”
mentioning
confidence: 91%
“…Elevated hospital admission blood pressure (BP) in patients with acute stroke is common 1 and is associated with poor outcomes. [2][3][4][5] There is limited randomized clinical trial evidence that acute BP reduction improves outcomes after intracerebral hemorrhage (ICH). …”
mentioning
confidence: 99%
“…[2][3][4][5] There is limited randomized clinical trial evidence that acute BP reduction improves outcomes after intracerebral hemorrhage (ICH). 6 One of the hypothesized reasons for the modest treatment effect is that hematoma enlargement and clinical deterioration have already begun by the time antihypertensive therapy is administered.…”
mentioning
confidence: 99%
“…Regardless of t-PA injection, a larger difference in SBP and DBP during the acute phase of ischemic stroke is associated with reduced survival after 3 months 15 , and worsened neurological symptoms within 7 days of admission 16 . Although the measurement method, timing, mathematical calculation of the blood pressure, as well as measures of the patient's prognosis, differed among these studies, the common claim in these papers is that changes in blood pressure are associated with patient's prognosis.…”
Section: Discussionmentioning
confidence: 99%